Brand Reputation as a Mediator in the Relationship Between Crisis Management and Hospitality Performance in Nigeria. - Sajuyigbe, Ademola Samuel; Umoru , Philomina Itunumen; Morakinyo, Dauda Ayodele; Tella, Rahman Adeniran; Igwe , Clara Obiageri; Egunjobi, Grace Oyejope; Oladeji, Adesola Alaba (FEB - Universitas Lampung, 2025)
The study examines the mediating effect of brand reputation on the relationship between crisis management factors such as stakeholder engagement, legal and ethical considerations, response coordination, and training and education, and guest satisfaction in the Nigerian hospitality industry. The primary data collection involved 195 structured questionnaires designed for hoteliers from the selected Hotels in Oyo State. Data analysis was performed with the aid of Path Analysis Structural Equation Modelling (PA-SEM) using STATA version 15. The results confirm that stakeholder engagement, legal and ethical considerations, response coordination, training and education, and brand reputation all have significant direct effects on guest satisfaction. Additionally, the study highlights the partial mediating effect of brand reputation on the relationship between crisis management parameters and guest satisfaction. This implies that while crisis management practices directly enhance guest experiences, the positive impact is further reinforced when a strong brand reputation is maintained. A well-managed brand identity, particularly during crises, fosters customer trust and loyalty, ultimately leading to higher guest satisfaction. Subsequently, the study provides practical recommendations for hospitality businesses to enhance resilience, improve guest experiences, and maintain competitive advantage in the face of crises.